Food Systems Innovation to Nurture Equity and Resilience Globally (Food SINERGY): insights from the Food SINERGY network - Ana Deaconu; Malek Batal; Claudia Irene Calderón; Patrick Caron; Jessica McNally; Emile Frison; Geneviève Mercille; Mylène Riva; Ben Brisbois (FACETS)
The international collaboration network Food Systems Innovation to Nurture Equity and Resilience Globally (Food SINERGY) unites food system experts concerned with the confluence of environmental, geopolitical, economic, and public health stressors that weaken food systems and increase inequalities. In March 2023, Food SINERGY participants from universities, research institutes, food policy advocacy groups, Indigenous networks, farmers’ associations, consumer organizations, social enterprises, and non-governmental organizations from around the world met in Mont Orford, Québec, for a forum to revisit food system structures across local-to-global scales and to identify key junctures for transformation. This article summarizes the network's discussions in the context of the existing literature. Key knowledge contributions include the importance of diversification throughout the food system for cultivating resilience; the value of food sovereignty in promoting equity across scales; the reconciliation between food sovereignty and equitable trade; the need for consonance between policy environments at different scales to enable positive societal actions; the pioneering role of food system innovations that challenge conventional political and economic structures, with emphasis on agroecology; and the need for critical self-reflection around knowledge production and knowledge use to better serve equitable food systems. These discussion outcomes provide insights for actors seeking to transform food systems in support of equity and resilience.